Interpretation of spatiotemporal gravity changes accompanying the earthquake of 21 August 2017 on Ischia (Italy) - BERRINO, Giovanna; VAJDA, Peter; ZAHOREC, Pavol; CAMACHO, Antonio G.; DE NOVELLIS, Vincenzo; CARLINO, Stefano; PAPČO , Juraj; BELLUCCI SESSA, Eliana; CZIKHARDT, Richard (Contributions to Geophysics and Geodesy, 2021)
We analyse spatiotemporal gravity changes observed on the Ischia island (Italy) accompanying the destructive earthquake of 21 August 2017. The 29 May 2016 to 22 September 2017 time-lapse gravity changes observed at 18 benchmarks of the Ischia gravimetric network are first corrected for the gravitational effect of the surface deformation using the deformation-induced topographic effect (DITE) correction. The co-seismic DITE is computed by Newtonian volumetric integration using the Toposk software, a high-resolution LiDAR DEM and the co-seismic vertical displacement field derived from Sentinel-1 InSAR data. We compare numerically the DITE field with its commonly used Bouguer approximation over the island of Ischia with the outcome that the Bouguer approximation of DITE is adequate and accurate in this case. The residual gravity changes are then computed at gravity benchmarks by correcting the observed gravity changes for the planar Bouguer effect of the elevation changes at benchmarks over the same period. The residual gravity changes are then inverted using an inversion approach based on model exploration and growing source bodies, making use of the Growth-dg inversion tool. The found inversion model, given as subsurface time-lapse density changes, is then interpreted as mainly due to a co-seismic or post-seismic disturbance of the hydrothermal system of the island. Pros and weak points of such interpretation are discussed.